Folkhemmets demokrati - En analys av den svenska socialdemokratins språkbruk kring demokratiska deltagandeformer - Friberg, Anna (Slagmark - Tidsskrift for idéhistorie, 2018)
This article investigates the role that civic participation played for the formation of the concept of democracy, by surveying the language of The Swedish Social Democratic Party (SAP) in the 1920s. During the first half of the decade, the SAP outlined various forms of participation for the citizens. Having adopted the traditionally conservative concept of the People’s Home, the party increasingly used it as a metaphor for the fully democratized society. This, however, created a tension between the Social Democrats’ arguments about the importance of civil participation in a democratic society, and the idea of the state building the People’s Home for the citizens. Using theoretical insights from conceptual history as the point of departure, this article addresses this tension by showing that according to the SAP, the fully democratic society could be realized at two levels: both by the state and by the citizens themselves.